2022
DOI: 10.1002/lio2.824
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of multifocal papillary thyroid cancer: A systematic review and meta‐analysis

Abstract: Objective: Papillary thyroid cancer (PTC) is the most common endocrine malignancy with a steadily increasing incidence. Researches have reported that tumor multifocality occurs in an extensive number of cases. Nevertheless, the clinical characteristics and prognostic value remained controversial. This study was performed to investigate the relationship between multifocal PTC and adverse clinicopathologic features and the prognosis.Methods: A systematic review and meta-analysis were conducted based on three ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…However, they did not focus on low-risk patients only and the subsequent de-escalation movement. A recent review and meta-analysis by Cui et al ( 21 ) reported on the clinical outcomes of multifocal PTC and showed that multifocal disease is more aggressive in contrast to unifocal disease and that it is accompanied by an increased risk of recurrence. They did not mention bilaterality.…”
Section: Discussionmentioning
confidence: 99%
“…However, they did not focus on low-risk patients only and the subsequent de-escalation movement. A recent review and meta-analysis by Cui et al ( 21 ) reported on the clinical outcomes of multifocal PTC and showed that multifocal disease is more aggressive in contrast to unifocal disease and that it is accompanied by an increased risk of recurrence. They did not mention bilaterality.…”
Section: Discussionmentioning
confidence: 99%
“…3 Many meta-analytic studies have found that multifocal PTC is associated with progression and recurrence. [4][5][6][7] Feng et al reported on multifocal PTC (n = 157, 24.7%) in their retrospective study of data from 635 PTC patients; also showing multifocality to be associated with an increased risk of recurrence, lymph node metastases, vascular invasion, and extra-thyroidal extension, that, moreover, increased the more tumor foci were present. 8 On the other hand, Harach et al reported the common occurrence of occult PTC (52 foci in 36 thyroids) in their autopsy study (n = 101), 10 of which showed multifocality with 2-5 foci.…”
Section: Introductionmentioning
confidence: 99%
“…This may be reflected in the clinical and prognostic importance of multifocality still being controversial 3 . Many meta‐analytic studies have found that multifocal PTC is associated with progression and recurrence 4–7 . Feng et al reported on multifocal PTC ( n = 157, 24.7%) in their retrospective study of data from 635 PTC patients; also showing multifocality to be associated with an increased risk of recurrence, lymph node metastases, vascular invasion, and extra‐thyroidal extension, that, moreover, increased the more tumor foci were present 8 .…”
Section: Introductionmentioning
confidence: 99%
“…There have been major changes in the management of lowrisk differentiated thyroid cancer (DTC) over the period of 2000 to 2018, consistent with the American Thyroid Association (ATA) guidelines, which suggest less extensive surgical management of low-risk tumors (1,2). The proportion of thyroid lobectomy rather than total thyroidectomy slightly increased during the 2014-2018 period (1).…”
mentioning
confidence: 99%